Clinical aspects of dento-maxillary abnormalities to the members of the same family - Mioara Decusară; Anamaria Zaharescu; Ada Ștefănescu; Delia Daragiu; Dorina-Cerasella Șincar (Amaltea Medical Publishing House, 2020)
Dento-maxillary abnormalities are considered to be the consequence of the problems of quantitative development of position, direction and rhythm of the three elements of the dento-maxillary apparatus (teeth, alveolis and maxillary bones), associated with occlusal and neuro-muscular functional disorders. Heredity plays an important role in triggering this process, but also, the local, general and environmental factors, which intervene prenatally and postnatally, so that, to rhe members of the same family, the clinic and the evolution of dento-maxillary anomalies may present different aspects. The purpose of this article is to present some clinical aspects of dento-maxillary anomalies in members of the same family (parents, siblings). The cases were selected from a group of 386 patients treated for a period of 40 months in a private orthodontic practice in Brăila. The research of the etiology of a dento-maxillary anomaly as a hereditary determinism allows the application of a treatment adapted to the clinical case.